Situation Report: Hungary, 15 June 1977 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Kadar's Visit to Italy and Papal Audience 1977 Agreement on Horticulture Export to the Soviet Union Signed Kindergartens Still Fall Short of Demand Radio Budapest Likes The Master and Margarita